Energy, Wealth and Governance in the Caucasus and Central Asia - Auty, Richard; de Soysa, Indra (Central Asia Research Forum, 2006)
Drawing upon recent progress in development economics and political science, the book provides fresh analysis of the Caucasus and Central Asia (CCA) countries transition to a market economy by tracing the impact of natural resource endowment. The book examines the synergies between energy-rich and energy-poor states and highlights the practical consequences of both well-managed and poorly-managed deployment of energy. Featuring contributions from prominent specialists on resource-driven economies, the book argues that unless CCA elites change the way in which they deploy natural resource, revenues regional development will fall short of its potential with possible disastrous consequences. The contributors apply the experience of the developing market economies to demonstrate that the region still holds considerable potential to become an important, stable supplier of raw materials and a source of industrial demand to the global economy. However, the CCA is equally likely to become a threat to the global economy as a consequence of the misuse of energy revenues to promote the interests of predatory political elites.